Critical evaluation of Pakistan's counter-narrative efforts. Issue 2 (4th May 2019) - Iqbal, Khuram; Zafar, Saad Kalim; Mehmood, Zahid
ABSTRACT: Counter-narrative is considered an integral component of soft counter-terrorism approaches. This paper examines the case study of Egypt and Pakistan, while keeping the former as a reference point to critically evaluate the counter-narrative campaign of the latter in light of Aristotle's classic work 'Rhetoric'. Credibility and character of messenger, according to Aristotle, is the most potent weapon in one's rhetorical arsenal. The paper argues that the public narrative produced and disseminated by the state of Pakistan contains all necessary elements of effective persuasion sans credible messengers, who should ideally come from the peer group of target audience. Besides highlighting the need for a credible messenger, we propose some policy interventions aimed at projecting the state as a responsible and motherly entity. The paper concludes that the state narrative can successfully recapture its political and moral legitimacy through portraying her role not only as the custodian of Islam and defender of Pakistani Muslims but also the provider of equal economic opportunities, good governance and swift justice.